2012
DOI: 10.1177/0192623312444029
|View full text |Cite
|
Sign up to set email alerts
|

Off-Target Platelet Activation in Macaques Unique to a Therapeutic Monoclonal Antibody

Abstract: AMG X, a human neutralizing monoclonal antibody (mAb) against a soluble human protein, caused thrombocytopenia, platelet activation, reduced mean arterial pressure, and transient loss of consciousness in cynomolgus monkeys after first intravenous administration. In vitro, AMG X induced activation in platelets from macaque species but not from humans or baboons. Other similar mAbs against the same pharmacological target failed to induce these in vivo and in vitro effects. In addition, the target protein was kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 47 publications
1
28
1
Order By: Relevance
“…There were no effects on the coagulation cascade, with no changes in coagulation times (prothrombin time and activated partial thromboplastin time) and minor increases, rather than decreases, in fibrinogen concentration. The lack of spontaneous external hemorrhage in cynomolgus monkeys with profound thrombocytopenia has been previously reported (Santostefano et al 2012). In the relatively protected environment of a laboratory animal facility, the cynomolgus monkeys on this study with very low platelet counts but normal coagulation parameters had no episodes of clinically relevant spontaneous hemorrhage.…”
Section: Thrombocytopenia and Rbc Decreases Were Notmentioning
confidence: 69%
See 1 more Smart Citation
“…There were no effects on the coagulation cascade, with no changes in coagulation times (prothrombin time and activated partial thromboplastin time) and minor increases, rather than decreases, in fibrinogen concentration. The lack of spontaneous external hemorrhage in cynomolgus monkeys with profound thrombocytopenia has been previously reported (Santostefano et al 2012). In the relatively protected environment of a laboratory animal facility, the cynomolgus monkeys on this study with very low platelet counts but normal coagulation parameters had no episodes of clinically relevant spontaneous hemorrhage.…”
Section: Thrombocytopenia and Rbc Decreases Were Notmentioning
confidence: 69%
“…Adverse events associated with therapeutic mAbs are often related specifically to binding of a target moiety or to modifying an intended biochemical pathway (Kamba and McDonald 2007). Recently, several publications have documented nontarget-related effects of mAbs on peripheral blood cells (Martin et al 2008;Rudmann et al 2011;Adis, 2002;Santostefano et al 2012). Each of these examples has shown unique characteristics with respect to cells affected, affinity of the unintended Purified monocytes were incubated with CMFDAlabeled platelets and isotype control, positive control W6/32, and mAbY.1 at 3 concentrations for 6 hr.…”
Section: Thrombocytopenia and Rbc Decreases Were Notmentioning
confidence: 99%
“…One example that has been given some more attention, and for which data have been published, is a case where thrombocytopenia occurred after administration of a mAb under development, whereas this did not happen with four other mAbs directed at the same pharmacological target. 26 In this case, the mAbs had the same target, but were not biosimilars. Subsequently it was shown that the functional differences between these antibodies had a structural basis: The unexpected toxicity was shown to be driven by one to three amino acid differences in the light chain.…”
Section: Safety Evaluationmentioning
confidence: 99%
“…Included in these experiments was the use of a variety of techniques such as classic clinical pathology and immunotoxicology assays, flow cytometry, immunocytochemistry, and histology. AMG X caused marked thrombocytopenia, platelet activation, transient loss of consciousness, and reduced mean arterial pressure in cynomolgus monkeys at doses 15 mg/kg after the first intravenous administration (Santostefano et al 2012). First, Everds and her colleagues provided evidence that the effect was off-target by showing that the pharmacological target was not expressed in platelets and that other mAbs against the same target failed to induce the in vivo platelet effects.…”
mentioning
confidence: 99%
“…(Morris et al 2010;Waser et al 2011) Are there differences in the affinity of the test agent with the affected tissue or cell type or pathway that may explain the species differences? (Rudmann et al 2012;Santostefano et al 2012) Is there a correlative biomarker that can be monitored preclinically in the sensitive species that is translatable clinically? (Knudsen et al 2010) 312 RUDMANN TOXICOLOGIC PATHOLOGY thrombocytopenia (nadir *3,000 platelets/uL) with mild-tomarked decreases in red cell mass.…”
mentioning
confidence: 99%